Transcriptome‐derived microsatellite markers for Dioon (Zamiaceae) cycad species1. (12th February 2016) - Prado, Alberto; Cervantes‐Díaz, Fret; Perez‐Zavala, Francisco G.; González‐Astorga, Jorge; Bede, Jacqueline C.; Cibrián‐Jaramillo, Angélica
Abstract : Premise of the study: Dioon (Zamiaceae) is an endangered North American cycad genus of evolutionary and ornamental value. We designed and validated a set of microsatellite markers from D. edule that can be used for population‐level and conservation studies, and that transferred successfully to D. angustifolium, D. spinulosum, and D. holmgrenii . Methods and Results: We tested 50 primers from 80 microsatellite candidate loci in the OneKP D. edule transcriptome. Genotypes from 21 loci in 20 D. edule individuals revealed up to 14 alleles per locus and observed heterozygosity from 0.15 to 0.92; one locus was monomorphic. Seven of those 21 loci were polymorphic in D. angustifolium, D. spinulosum, and D. holmgrenii, with up to seven alleles, and an observed heterozygosity up to 0.89. Conclusions: The transcriptome‐derived microsatellites generated here will serve as tools to advance population genetic studies and inform conservation strategies of Dioon, including the identification and origin of illegal plants in the cycad trade.